Sustainable Digital Talent Ecosystem in the New Era: Impacts on Businesses, Governments and Universities - Karaboga, Tugba; Gurol, Yonca Deniz; Binici, Ceylan Merve; Sarp, Pinar (ISTANBUL UNIV, SCH BUSINESS, 2020)
Future work will become more digital-oriented and the term digital talent will become the essence of the future workforce. In a digital work design, digital talents, digital fluency, digital networks, and digital platforms will be the most pronounced words. As a result of the rapid digital transformation effort all over the world, the huge increase in the demand for digital skills has led to a worldwide digital talent gap. To close this gap and to expand the digital talent ecosystem in a country, corporations, governments, and higher education institutions should act together. Universities have to understand the digital capability needs of employers to prepare digitally employable graduates for digitally dominated business environments. Governments should attract digital talents to simplify and digitize their services and operations. Corporations should attract digital talents to succeed in digital transformation and gain a competitive advantage. In this study, we emphasized the effect of digital transformation and digital talent shortage on governments, corporations, and universities. Then we highlighted the importance of their collaboration to develop and sustain digitally talented people in a country. We hope this study will be an encouraging guide to enhance partnerships between governments, corporations, and universities to better manage the digital talent shortage.
Keywords: Digital talent management; digital transformation; government role; corporation role; university role; TRANSFORMATION; Business & Economics